Reading Anxiety Among Junior High School Students in Mataram: A Survey Study - Kharismanto, Arif Nugroho; Farani, Rizki (Journal of English and Education (JEE), 2022)
This study aims to identify reading anxiety among junior high school students. The research design employed a quantitative approach in the form of a survey study. There were 80 respondents who were willing to participate in this study. The respondents were students from one of junior high schools in Mataram, Indonesia.  All respondents were students from grades 8 and 9. To collect the data, this study adapted a questionnaire from Ahmad et.al. (2013) which consists of five domains of reading anxiety, i.e., (1) lack of vocabulary, (2) unfamiliar topic, (3) unfamiliar culture, (4) afraid of making errors, and (5) worry about reading effects. Based on the results, the statement with the highest score is “I enjoy reading a text in English text in English when I know its translation” (M=4.15; SD=.730). Meanwhile, the statement with the lowest score is “In reading aloud in the class I do not understand the text even though it is easy” (M=3.00; SD=1.055). The data imply that the most significant factor in students’ reading anxiety is lack of vocabulary and the least factor is worrying about reading effects.